2021
DOI: 10.1186/s12884-020-03487-6
|View full text |Cite
|
Sign up to set email alerts
|

A woman with disseminated tuberculosis experienced preterm delivery, fallopian tube pregnancy, and delivered successfully following in vitro fertilization: a case report

Abstract: Background Disseminated tuberculosis (TB) is a fatal disease resulting from hematogenous dissemination of Mycobacterium tuberculosis. Spontaneous pregnancy rate of women with TB is low; furthermore, live birth, spontaneous abortion or ectopic pregnancy may be the outcomes even if pregnancy occurs. Case presentation We report a case of a woman with disseminated TB who had a series of complications including preterm delivery with congenital TB and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…For new cases, whether microbiologically confirmed or clinically diagnosed and drug-sensitive, previously treated patients, including nonresponders, failures, recurrent TB, and loss to follow up for one month after receiving one month of antitubercular therapy (ATT), are given combination therapy. Medical therapy with antitubercular drugs is effective for FGTB [24][25][26][27][28][29].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For new cases, whether microbiologically confirmed or clinically diagnosed and drug-sensitive, previously treated patients, including nonresponders, failures, recurrent TB, and loss to follow up for one month after receiving one month of antitubercular therapy (ATT), are given combination therapy. Medical therapy with antitubercular drugs is effective for FGTB [24][25][26][27][28][29].…”
Section: Treatmentmentioning
confidence: 99%
“…A 31year-old woman with FGTB and fallopian tube involvement underwent a laparoscopic salpingostomy followed by regular 3 Infectious Diseases in Obstetrics and Gynecology ATT for two years. In vitro fertilization-embryo transfer (IVF-ET) gave birth to a healthy baby girl through vaginal after 36 weeks of pregnancy [24]. A comparative study of 38 infertile women with FGTB undergoing salpingectomies and treated with ATT for 6-12 months demonstrated that salpingectomy is a definitive and effective treatment option.…”
Section: Treatmentmentioning
confidence: 99%